Abnormally High Power Output of Wind Turbine in Cold Weather: A Preliminary Study - Christophe Leclerc; Christian Masson (International Journal of Rotating Machinery)
According to popular belief, air temperature effects on wind turbine power output are produced solely by air density variations, and power is proportional to air density. However, some cases have been reported, all involving stall-controlled wind turbines, in which unexpected high power output was observed at very low temperatures.